Peripheral skin cooling during hyper-gravity: hemodynamic reactions - Kagelmann, Niklas; Janke, David; Maggioni, Martina Anna; Gunga, Hanns-Christian; Riveros Rivera, Alain; Genov, Magdalena; Noppe, Alexandra; Habazettl, Helmut; Bothe, Tomas Lucca; Nordine, Michael; Castiglioni, Paolo; Opatz, Oliver (Frontiers in Physiology, 2023)
Orthostatic dysregulation occurs during exposure to an increased gravitational vector and is especially common upon re-entering standard Earth gravity (1g) after an extended period in microgravity (0g). External peripheral skin cooling (PSC) has recently been described as a po-tent countermeasure against orthostatic dysregulation during heat stress and in lower body negative pressure (LBNP) studies. We therefore hypothesized that PSC may also be an effec-tive countermeasure during hyper-gravity exposure (+Gz). To investigate this, we designed a randomized short-arm human centrifuge (SAHC) experiment (“Coolspin”) to investigate whether PSC could act as a stabilizing factor in cardiovascular function during +Gz. Artificial gravity between +1g and +4g was generated by a SAHC. 18 healthy male volun-teers completed two runs in the SAHC. PSC was applied during one of the two runs and the other run was conducted without cooling. Each run consisted of a 10-min baseline trial fol-lowed by a +Gz step protocol marked by increasing g-forces, with each step being 3min long. The following parameters were measured: blood pressure (BP), heart rate (HR), stroke volume (SV), total peripheral resistance (TPR), cardiac output (CO). Furthermore, a cumulative stress index for each subject was calculated. +Gz led to significant changes in primary as well as in secondary outcome parameters such as HR, SV, TPR, CO, and BP. However, none of the primary outcome parameters (HR, cumula-tive stress-index, BP) nor secondary outcome parameters (SV, TPR, CO) showed any signifi-cant differences – whether the subject was cooled or not cooled. Systolic BP did, however, tend to be higher amongst the PSC group. In conclusion, PSC during +Gz did not confer any significant impact on hemodynamic activi-ty or orthostatic stability during +Gz. This may be due to lower PSC responsiveness of the test subjects, or an insufficient level of body surface area used for cooling. Further investiga-tions are warranted in order to comprehensively pinpoint the exact degree of PSC needed to serve as a useful countermeasure system during +Gz.